English teachers’ perceptions and constraint on the use of authentic assessment in teaching English - Riadi Syah Putra; Saiful Marhaban (Universitas Syiah Kuala, 2021)
This study aims to determine teacher perceptions of authentic assessment, and to find out the teacher's problems in implementing authentic assessment and solutions that can be done by English teachers in overcoming problems in implementing authentic assessment. In data collection, researchers used questionnaires, interviews and documentation to junior high school teachers in Banda Aceh, then analyzed the data using descriptive-quantitative analysis techniques. The results showed that the English teacher's perceptions of authentic assessment were in the medium category, starting from the teacher's absorption of authentic assessment information, understanding and assessing the authentic assessment of the 2013 Curriculum. learning so there is not enough time; teachers still do not understand the preparation of authentic assessment instruments and rubrics. Teachers still have difficulty sorting between the three aspects to be assessed, namely aspects of attitude, knowledge and skills; The teacher feels overwhelmed because if there are many students, a lot of time and money will be needed to implement authentic assessments; The teacher finds it difficult because they have to add up each score obtained by the students as a whole and then describe the value obtained. Finally, the teacher's efforts to overcome this difficulty by participating in peer discussion training between teachers, especially English teachers, as well as attending training and assistance by the Government or the Ministry of Education and higher education institutions.